Recurrent spontaneous fetal loss (RSFL) pada sindrom antifosfolipid - Wantania, John J. E. (UNIVERSITAS SAM RATULANGI, 2016)
Abstract: Approximately 40-50% causes of recurrent spontaneous fetal death, often called the recurrent spontaneous fetal loss (RSFL), could not be identified so far. Antiphospholipid syndrome itself is one of the most common causes of RSFL and is responsible for approximately 16-36% of patients with RSFL. Various factors associated with the occurrence of the RSFL in APS are as follows: intrauterine growth restriction (IUGR), preeclampsia, premature placental separation, DVT, HELLP, and DIC at a normal fetal karyotype. Diagnosis includes clinical and laboratory criteria. Additional laboratory examinations have been developed and used to improve the predictive power and diagnostics. Repeat aPL antibodies examination may be required to increase the sensitivity and specificity of diagnosis. Other treatment options include the use of anticoagulants, corticosteroids, or any other modalities with regard to obsterics conditions.Keywords: recurrent spontaneus fetal loss, APSAbstrak: Sekitar 40-50% penyebab terjadinya kematian janin spontan berulang atau sering disebut pula dengan Recurrent Spontaneous Fetal Loss (RSFL) sampai saat ini tidak dapat diidentifikasi. Sindrom antifosfolipid sendiri adalah salah satu penyebab paling umum terjadinya RSFL dan bertanggung jawab pada sekitar 16-36% pasien dengan RSFL. Berbagai faktor yang terkait dengan terjadinya RSFL pada APS meliputi pertumbuhan janin intrauterin yang terhambat (IUGR), preeklampsia, pemisahan plasenta prematur, DVT, HELLP, dan DIC pada kariotipe janin yang normal. Diagnosis mencakup kriteria klinis dan laboratorium. Pemeriksaan laboratorium tambahan telah dikembangkan dan digunakan untuk meningkatkan kekuatan prediksi dan diagnostik. Pemeriksaan antibodi aPL berulang mungkin diperlukan untuk meningkatkan sensitivitas dan spesifisitas diagnosis. Pilihan penanganan antara lain dengan penggunaan antikoagulan, kortikosteroid, atau pun modalitas lain dengan tetap memperhatikan kondisi obsterik.Kata kunci: kematian janin spontan berulang, APS